Longitudinal Relationship of Leisure Activity Engagement With Cognitive Performance Among Non-Demented, Community-Dwelling Older Adults. (30th March 2021) - Armstrong, Nicole M; Tom, Sarah E; Harrati, Amal; Casaletto, Kaitlin; Pa, Judy; Arce Rentería, Miguel; Gu, Yian; Rajan, Kumar B; Schupf, Nicole; Fieo, Robert; Weuve, Jennifer; Simonsick, Eleanor M; et al.
Abstract: Background and Objectives: Leisure activity engagement (LAE) may reduce the risk of incident dementia. However, cognitive performance may predict LAE change. We evaluated the temporal ordering of overall and subtypes of LAE (intellectual, physical, and social) and cognitive performance (global, language, memory, and visuospatial function) among non-demented older adults. Research Design and Methods: The Washington Heights–Inwood Columbia Aging Project concurrently administered a survey measure of 13 leisure activities and a neuropsychological battery every 18–24 months for up to 14 years to 5, 384 racially and ethnically diverse participants. We used parallel process conditional latent growth curve models to examine temporal ordering in the overall sample and within baseline diagnostic groups (mild cognitive impairment [MCI] vs. cognitively normal). Results: Levels and changes of overall and subtypes of LAE were positively correlated with cognitive performance in the overall sample and within each diagnostic group. In the overall sample, higher initial memory was associated with slower declines in social LAE (estimate = 0.019, 95% confidence interval [95% CI]: 0.001–0.037). Among MCI, higher initial physical LAE was associated with slower declines in memory (estimate = 0.034, 95% CI: 0.001–0.067), but higher initial intellectual LAE was related to steeper declines in visuospatial function (estimate = −0.028, 95% CI: −0.052 to −0.004). Among cognitively normal, higher initial memory was associated with slower declines in intellectual LAE (estimate = 0.012, 95% CI: 0.002−0.022). Discussion and Implications: Dynamic interplay of LAE with cognitive performance was observed across diagnostic groups. Levels of LAE subtypes could be more predictive of change in certain cognitive domains within older adults with MCI.